Effects of Web-Based Learning and Cultural Literacy Towards Non-formal Educator Performance - Djibu, Rusdin; Duludu, Ummyssalam (Journal of Nonformal Education, 2021)
The purpose of this research is to find out: (1) the influence of Web-based learning with the performance of Educators, (2) the influence of cultural literacy with Educators' performance (3) the influence of Web-based learning and literary culture together with performance Educators. The method used in this study was with a quantitative approach with the ex-post-facto method. The population in this study was all non-formal educators working in the Gorontalo City learning activities workshop amounting to 107 people, while samples were 59 people using proportional random sampling. Data is collected through poll deployments. The conclusion to this research is (1) there is a positive influence on Web-based learning on educators' performance, which means that the better web-based learning is better for educator performance. (2) there is a positive influence on the cultural literacy of the educator's performance, meaning that both the literate culture is also the higher the performance of educators. (3) there is a positive influence on web-based learning and cultural literacy together to the performance of educators working in the Learning Activities workshop in Gorontalo city, this means that the higher the implementation of Web-based learning and culture of literacy, the higher the performance of non-formal educators.